The spatiotemporal transcriptional profiling of murine brain during cerebral malaria progression and after artemisinin treatment - Chen, Jiayun; Bai, Yunmeng; He, Xueling; Xiao, Wei; Chen, Lina; Wong, Yin Kwan; Wang, Chen; Gao, Peng; Cheng, Guangqing; Xu, Liting; Yang, Chuanbin; Liao, Fulong; et al. (Nature communications, 2025)
Cerebral malaria (CM) is a severe encephalopathy caused by Plasmodium parasite infection, resulting in thousands of annual deaths and neuro-cognitive sequelae even after anti-malarial drugs treatment. Despite efforts to dissect the mechanism, the cellular transcriptomic reprogramming within the spatial context remains elusive. Here, we constructed single-cell and spatial transcriptome atlases of experimental CM (ECM) male murine brain tissues with or without artesunate (ART) treatment. We identified activated inflammatory endothelial cells during ECM, characterized by a disrupted blood-brain barrier, increased antigen presentation, and leukocyte adhesion. We also observed that inflammatory microglia enhance antigen presentation pathway such as MHC-I to CD8 + cytotoxic T cells. The latter underwent an inflammatory state transition with up-regulated cytokine expression and cytotoxic activity. Multi-omics analysis revealed that the activated interferon-gamma response of injured neurons during ECM and persisted after ART treatment. Overall, our research provides valuable resources for understanding malaria parasite-host interaction mechanisms and adjuvant therapy development. By integrating single-cell and spatial transcriptomic analysis, Chen et al. profile the cellular disruptions in the murine brain during cerebral malaria and after artemisinin treatment.